2006
DOI: 10.3748/wjg.v12.i36.5913
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse gastroduodenitis and pouchitis associated with ulcerative colitis

Abstract: We experienced a very rare case of ulcerative colitis (UC) accompanied with analogous lesions in the stomach, duodenum, and ileal J-pouch. Ileal J-pouch anal anastomosis was performed on a 29-year old woman in 1996. Six years later, she was admitted again to our hospital because of epigastralgia, nausea, watery diarrhea and low fever. Based on the results of endoscopic examination, we diagnosed it as pouchitis. Moreover, on hypotonic duodenography, expansion of the duodenal bulb and the descending portion were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 8 publications
1
34
1
1
Order By: Relevance
“…UC is considered to be a multifactorial polygenic chronic inflammatory disease that predominantly affects the gastrointestinal system, with the potential also for systemic involvement, such as of the biliary tract, joints, skin and eyes [7,8,9]. Moreover, gastroduodenal lesions of UC have recently been reported, in addition to backwash ileitis and postcolectomy pouchitis [1,2,3,4,5,6]. It is thus not surprising that UC patients were also found to have small-bowel lesions, including reddened lesions and erosions, in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UC is considered to be a multifactorial polygenic chronic inflammatory disease that predominantly affects the gastrointestinal system, with the potential also for systemic involvement, such as of the biliary tract, joints, skin and eyes [7,8,9]. Moreover, gastroduodenal lesions of UC have recently been reported, in addition to backwash ileitis and postcolectomy pouchitis [1,2,3,4,5,6]. It is thus not surprising that UC patients were also found to have small-bowel lesions, including reddened lesions and erosions, in this study.…”
Section: Discussionmentioning
confidence: 99%
“…UC is traditionally regarded as predominantly involving the rectum and spreading proximally, generally sparing the alimentary canal proximal to the ileocecal valve. However, gastroduodenal lesions have also been reported recently in cases of UC, such as backwash ileitis and postcolectomy pouchitis [1,2,3,4,5,6]. Furthermore, some investigators have proposed that since UC is also commonly associated with extraintestinal involvement, such as of the biliary tract, anterior chamber of the eye and synovium, it should be considered as a systemic disease and not as a localized colonic disease [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports of gastroduodenitis have shown no response to proton pump inhibitors, although several reports indicated the oral intake of crushed mesalazine tablets to be effective (6,8). In the present case, the patient was initially unable to take crushed mesalazine tablets orally due to SMA syndrome.…”
Section: Discussionmentioning
confidence: 56%
“…Gastric and/or duodenal involvement has, rarely, been reported in association with UC. 29,30,[62][63][64][65][66] For instance, in a recent study by Lin et al, 65 esophageal, gastric and duodenal biopsies in 69 UC patients were compared with 97 non-UC controls. In that study, UC patients showed a higher prevalence rate of focal gastritis, basal mucosal mixed inflammation, superficial plasmacytosis and diffuse chronic, or chronic active, duodenitis (Figure 4).…”
Section: Uc With Crohn's-like Featuresmentioning
confidence: 99%